Produksi Lipid Dari Mikroalga Yang Tumbuh Di Air Gambut Dengan Penambahan Nutrisi BG-11 - Putri, Bella Nadiah; Elystia, Shinta; Muria, Sri Rezeki (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
One innovation in making biodiesel is from microalgae. The use of microalgae as a source of raw materials for biodiesel production requires biomass and high lipid content. The lipid content of microalgae can be converted into biodiesel. The purpose of this study is to look at the effect of the addition of micronutrients on the growth rate and lipid content of indigenous microalgae in peat water. Indigen microalgae as much as 50 mL were cultivated in 450 mL of peat water and BG-11 nutrients at a dose (0 mL / L, 0.5 mL / L, 1 mL / L and 1.5 mL / L) lasted 13 days. The results of the study, the highest cell count of 10.08 x 106 cells / mL and the highest lipid content of 34.8% in the addition of BG-11 nutrients by 1 mL / L. Keywords: Nutrition BG-11, Peat Water, Microalgae Indigeneous, Lipids